Implementation of Adequate Housing Fulfillment for the Poor by International Non-Governmental Organizations in Batam City (A Study on Habitat for Humanity) - Selfia Afriantita; Rina Shahriyani Shahrullah; Elza Syarief (Journal Equity of Law and Governance, 2025)
Everyone has the right to a decent standard of living, including the right to adequate housing. This right is enshrined in the Universal Declaration of Human Rights, the 1945 Constitution of the Republic of Indonesia, and Law No. 1 of 2011 concerning Housing and Settlements. However, in practice, there are still approximately 1,713 inadequate homes in Batam City, despite the existence of Batam City Regional Regulation No. 6 of 2019 on Housing and Settlement Management. Therefore, the aim of this study is to gain a deeper understanding of efforts to provide adequate housing in Batam City, particularly by Habitat for Humanity, using Soerjono Soekanto's Theory of Legal Effectiveness as an analytical tool. To achieve this objective, the study employs an empirical legal research method with a sociological approach, collecting primary data through observations and interviews, and secondary data through literature review. All data are analyzed qualitatively from a juridical perspective. The findings indicate that Habitat for Humanity adheres to international, national, and local regulations and involves the local community to ensure that the constructed homes meet the standards of adequate housing. However, Habitat for Humanity still faces challenges related to law enforcement, infrastructure, and cultural factors. To address these challenges, it is necessary to establish a regular coordination forum between BP Batam, the Batam City Government, and Habitat for Humanity, enhance basic infrastructure such as clean water and electricity, and optimize land use. Additionally, education and socialization on community cooperation that aligns with local culture, as well as adjustments to administrative procedures to facilitate community participation, are recommended.